2019
DOI: 10.2967/jnumed.119.236893
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Identifies Altered Brain Metabolism in Patients with Cri du Chat Syndrome

Abstract: Cri du chat syndrome (CDCS) is a rare genetic disease that is caused by a deletion in the short arm of chromosome 5 (5p) and has a variable clinical spectrum. To our knowledge, no study in the literature has ever applied 18 F-FDG PET/CT to investigate alterations in brain glucose metabolism in these subjects. The aims of this study were to detect differences in brain 18 F-FDG metabolism in CDCS patients with different clinical presentations and identify possible brain metabolic phenotypes of this syndrome. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Areas of hypometabolism were detected in the posterior cingulate cortex, inferior parietal gyrus, and dorsolateral frontal cortex. These areas represent novel findings, because the hypometabolic regions reported in the previous literature are the left temporal lobe, the right frontal subcallosal gyrus, the caudate body, the thalamus, the cerebellum, and the midbrain [12,18]. These areas' findings may be correlated with some clinical features of this patient, such as the movement disorder with the cerebellar hypometabolic finding.…”
Section: Pet Analysissupporting
confidence: 59%
See 1 more Smart Citation
“…Areas of hypometabolism were detected in the posterior cingulate cortex, inferior parietal gyrus, and dorsolateral frontal cortex. These areas represent novel findings, because the hypometabolic regions reported in the previous literature are the left temporal lobe, the right frontal subcallosal gyrus, the caudate body, the thalamus, the cerebellum, and the midbrain [12,18]. These areas' findings may be correlated with some clinical features of this patient, such as the movement disorder with the cerebellar hypometabolic finding.…”
Section: Pet Analysissupporting
confidence: 59%
“…At the same time, aged 28 years old, the patient underwent a 18f-fluorodeoxyglucose ( 18 F-FDG) Positron Emission Tomography (PET)/computed tomography (CT) scan of the brain to investigate alterations in brain glucose metabolism. This investigation was performed with the aim of detecting differences in brain 18 F-FDG metabolism in CdC patients with different clinical presentations and to identify possible brain metabolic phenotypes of this syndrome [12].…”
Section: Case Reportmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report demonstrating a hypermetabolic pattern in the primary and premotor areas in patients with iNPH [18]. We could postulate that hypermetabolism may be determined by synaptic hyperactivity, contributing itself to motor symptoms in these patients, since these regions are connected to the spinal cord via the cortico-ponto-cerebellar pathway [19,20]. Increased astrocytosis, a sign of microglial activation, has been associated with 18 F-FDG hypermetabolism in other diseases [21].…”
Section: Discussionmentioning
confidence: 98%
“…The only anatomical and functional available observation in patients with CdC was provided by Cistaro, et al using ( 18) F-fluorodexyglucose PET, who observed in six cases that the main hypometabolic region detected was the left inferior temporal and homolateral temporal pole cortex (Broadman area 20, 34 36, 38) [19]. These regions are involved in verbal production and comprehension, working memory and selective attention to speech.…”
Section: Discussionmentioning
confidence: 99%